2015
DOI: 10.1136/bmjopen-2015-008197
|View full text |Cite
|
Sign up to set email alerts
|

Diet and physical activity for children's health: a qualitative study of Nepalese mothers’ perceptions

Abstract: ObjectivesNon-communicable diseases account for 50% of all deaths in Nepal and 25% result from cardiovascular diseases. Previous studies in Nepal indicate a high burden of behavioural cardiovascular risk factors, suggesting a low level of knowledge, attitude and practice/behaviour regarding cardiovascular health. The behavioural foundation for a healthy lifestyle begins in early childhood, when mothers play a key role in their children's lives. This qualitative study, conducted in a Nepalese peri-urban communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 36 publications
5
23
0
Order By: Relevance
“…Those who are prehypertensive must be fi rmly and unambiguously advised to practice lifestyle modifi cation to reduce their risk of developing hypertension in the future 42 . This is particularly true for the mothers in our study, because maintaining an unhealthy lifestyleis likelyto not only adversely affect their own health but may also negatively infl uence their children's choices regarding diet and physical activity 25 .…”
Section: Association Of Prehypertension With Obesity Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…Those who are prehypertensive must be fi rmly and unambiguously advised to practice lifestyle modifi cation to reduce their risk of developing hypertension in the future 42 . This is particularly true for the mothers in our study, because maintaining an unhealthy lifestyleis likelyto not only adversely affect their own health but may also negatively infl uence their children's choices regarding diet and physical activity 25 .…”
Section: Association Of Prehypertension With Obesity Parametersmentioning
confidence: 98%
“…Cardiovascular health emerged as an important but neglected issue in this community, particularly from the primary prevention perspective [22][23][24] . The aim of this paper was to specifi cally focus on mothers with children aged 1-7 years as mothersare the ones who are most involved in their children's behaviours related to cardiovascular risk factors including diet and physical activity 25 . We therefore estimated the extent of high blood pressure among mothers with emphasis on the concept of prehypertension and its association with obesity parameters.…”
mentioning
confidence: 99%
“…Likewise, we put the upper cut off at ten years as the mothers in our focus groups had expressed that it was very difficult to influence dietary and physical activity behaviour of those above 10 years or so. 14 We intended to include all these households in our sample.…”
Section: Methodsmentioning
confidence: 99%
“…14 Indeed, many factors determine children's eating habits and physical activity, 15,16 of which their preference for a particular food and activity can be a strong determinant. 17 This aspect has been studied mainly in high-income countries.…”
mentioning
confidence: 99%
“…Even though mothers may know that factors such as quality, quantity, and variety are important to a healthy diet, it is possible to think that they are not always able to identify what kind of food are really healthy, what are the appropriate quantities recommended for themselves or their children, and how varied a diet should be to be effectively considered healthy. In this direction, a qualitative study conducted with mothers of school children, with a socio-economic level similar to those of the present study, identified that, although the mothers recognized the importance of healthy lifestyle habits and a healthy diet for their own health and that of their children, they had considerable difficulty in identifying what was contemplated within this concept, regardless of their educational level (Oli, Vaidya, Subedi, Eiben, & Krettek, 2015). In that study, they showed to have some appropriate concepts, such as considering ultra-processed foods to be incompatible with a healthy diet, also observed in the present study, as well as others that were inappropriate or contradictory, such as considering a healthy diet to be bland or appropriate only for sick people (Oli et al, 2015).…”
mentioning
confidence: 99%